The influence of Hymer's dissertation on the theory of foreign derect investment - Dunning, John H.; Rugman, Alan M. (American Economic Review, 1985)
The great contribution of Stephen Hymer's seminal dissertation (1960) was to escape from the intellectual straightjacket of neoclassical-type trade and financial theory, and move us towards an analysis of the multinational enterprise (MNE) based upon industrial organization theory. The magnitude of this breakthrough can be put into perspective by considering the state of the art when Hymer wrote twenty-five years ago. In 1960 the prevailing explanation of international capital movements relied exclusively upon a neoclassical financial theory of portfolio flows. In this frictionless world of perfect competition, with no transaction costs, capital moves in response to changes in interest rate (or profit) differentials (see Carl Iversen, 1936). According to this arbitrage theory, capital is assumed to be transacted between independent buyers and sellers, that is, there is no role for the MNE. At the time there was no separate theory of foreign direct investment (FDI). The work did not even ask the question, of Why is there FDI?, despite the evidence of sectoral cross investments and the existence of large MNEs with intra-industry trade. If anything, the early work on FDI focused upon the where of investment in a particular nation or industry, for example, Dunning (1958) was chiefly interested in explaining U.S. FDI in Britain. There was little interest in understanding the reasons for the MNE, or the nature of its operations. The pioneering conceptual insight of Hymer was to break out of the arid mold of international trade and investment theory and focus attention upon the MNE per se. This permits us to treat FDI as a modality by which firms extend their territorial horizons abroad. The unique feature of FDI is a mechanism by which the MNE maintains control over productive activities outside its national boundaries, that is, FDI means international production. In this view, FDI is more than a process by which assets or claims are exchanged internationally (see Robert Aliber, 1970; 1983). Hymer's great insight was in focusing attention upon the MNE as the institution for international production, rather than international exchange. Until Hymer articulated the process of FDI as an international extension of industrial organization theory, it was not possible to understand why the MNE transfers intermediate products such as knowledge or technology among its units across different nations while still retaining property rights over such assets. Today it is widely recognized that the theory of FDI (i.e., international production) is primarily about the transfer of nonfinancial and ownershipspecific intangible assets by the MNE, which needs to appropriate and control the rate of use of its internalized advantage(s), see Rugman (1981), David Teece (1981; 1982), Richard Caves (1982) and Mark Casson (1983). In this paper we first acknowledge Hymer's contribution to the theory of FDI and then move on to reinterpret his dissertation in the light of the modern theory of the MNE. We tDiscussants: Raymond Vernon, Harvard University; Robert Z. Aliber, University of Chicago; Paul Streeten, Boston University.